2021
DOI: 10.1111/ele.13848
|View full text |Cite
|
Sign up to set email alerts
|

Body size and digestive system shape resource selection by ungulates: A cross‐taxa test of the forage maturation hypothesis

Abstract: The forage maturation hypothesis (FMH) states that energy intake for ungulates is maximised when forage biomass is at intermediate levels. Nevertheless, metabolic allometry and different digestive systems suggest that resource selection should vary across ungulate species. By combining GPS relocations with remotely sensed data on forage characteristics and surface water, we quantified the effect of body size and digestive system in determining movements of 30 populations of hindgut fermenters (equids) and rumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 90 publications
(137 reference statements)
3
28
0
Order By: Relevance
“…Possibly, low EVI values are indicative of open woodland. Giraffe and hartebeest preferred areas with medium vegetation productivity, broadly supporting the forage maturation hypothesis (Esmaeili et al, 2021). Giraffe and zebra preferred low elevation areas while hartebeest and buffalo favored flatter areas, as these areas may likely provide relative good visibility and low movement costs (Anderson et al, 2016).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Possibly, low EVI values are indicative of open woodland. Giraffe and hartebeest preferred areas with medium vegetation productivity, broadly supporting the forage maturation hypothesis (Esmaeili et al, 2021). Giraffe and zebra preferred low elevation areas while hartebeest and buffalo favored flatter areas, as these areas may likely provide relative good visibility and low movement costs (Anderson et al, 2016).…”
Section: Discussionsupporting
confidence: 69%
“…To address our research goal of assessing and understanding the ecological effectiveness of PAs in western Tanzania, we aimed at: (i) analyzing the patterns of cropland expansion across different protection categories over time; (ii) analyzing population trends of six large ungulate populations (buffalo Syncerus caffer , elephant Loxodonta africana , giraffe Giraffa camelopardalis , hartebeest Alcelaphus buselaphus , topi Damaliscus korrigum , and zebra Equus burchellii ) across areas with different protection categories over time; and (iii) generating species‐specific models to identify key ecological and anthropogenic spatial variables associated with the presence of the target species. We hypothesized that: (i) the extent of cropland within all areas would show an increasing trend over time and that the increase in cropland would be particularly pronounced on unprotected land; (ii) population trajectories of target species would be particularly negative in unprotected or less strictly PAs and be constant or only slightly negative in strictly PAs; (iii) target species would prefer the NP and areas distant to cropland; and (iv) the distribution of target species would be mediated by environmental variables, such as preferences for areas near rivers and areas with intermediate primary productivity (Esmaeili et al, 2021). Our findings can be used in implementing conservation plans beyond PA boundaries and can provide information on how different conservation categories affect conservation outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, movement may also be constrained by traits that we did not consider in this study. For example, recent work by Esmaeili et al (2021) found that digestive strategy in large mammals, i.e., fore-versus hind-gut fermentation, influences patterns of landscape use. We hope the present study will encourage researchers to measure these forms of movement for other types of organisms, and to expand on the types of movement considered.…”
Section: Discussionmentioning
confidence: 99%
“…This holds especially true for wild ungulates, as many species track resources across vast areas by following landscape-wide wavelike greening patterns (e.g., Bischof et al, 2012). Through this they increase forage quality by tracking plant maturation stages of high nutritional value (Fryxell, 1991;Esmaeili et al, 2021) or the duration of the experienced green season (Aikens et al, 2020). At the same time, when larger herbivores can reach and leave places at the right times (Holdo et al, 2007) and in critical densities, grazing stimulates the growth of many grassland plant species.…”
Section: Introductionmentioning
confidence: 99%
“…Resource-tracking ungulates have been studied frequently in temperate regions (e.g., Bischof et al, 2012;Geremia et al, 2019;Aikens et al, 2020;Esmaeili et al, 2021), and an important framework which unites optimal foraging theory and landscape ecology is available (Abrahms et al, 2021). However, very high resolution, vegetation-type specific and fence-oriented analyses are scarce, especially in semi-arid environments with scattered distributed resources.…”
Section: Introductionmentioning
confidence: 99%